Microfluidic platform for 3D cell culture with live imaging and clone retrieval. Issue 14 (23rd June 2020) - Mulas, Carla; Hodgson, Andrew C.; Kohler, Timo N.; Agley, Chibeza C.; Humphreys, Peter; Kleine-Brüggeney, Hans; Hollfelder, Florian; Smith, Austin; Chalut, Kevin J.
Abstract : 3D cell culture and microfluidic platform for monitoring biological process and single clone retrieval for downstream molecular or functional analysis. Abstract : Combining live imaging with the ability to retrieve individual cells of interest remains a technical challenge. Combining imaging with precise cell retrieval is of particular interest when studying highly dynamic or transient, asynchronous, or heterogeneous cell biological and developmental processes. Here, we present a method to encapsulate live cells in a 3D hydrogel matrix, via hydrogel bead compartmentalisation. Using a small-scale screen, we optimised matrix conditions for the culture and multilineage differentiation of mouse embryonic stem cells. Moreover, we designed a custom microfluidic platform that is compatible with live imaging. With this platform we can long-term culture and subsequently extract individual cells-in-beads by media flow only, obviating the need for enzymatic cell removal from the platform. Specific beads may be extracted from the platform in isolation, without disrupting the adjacent beads. We show that we can differentiate mouse embryonic stem cells, monitor reporter expression by live imaging, and retrieve individual beads for functional assays, correlating reporter expression with functional response. Overall, we present a highly flexible 3D cell encapsulation and microfluidic platform that enables both monitoring of cellular dynamics and retrieval for molecular and functional assays.